Factores socio-ambientales y de conservación en predios amazónicos de Ecuador vinculados o no al Programa Socio Bosque - Yánez, Patricio (2016)
This study explores issues related to the conservation of forests of western Ecuador's Amazon region (provinces of Napo, Pastaza and Morona Santiago) and its relationship with some social and economic variables, the forests were included or not to the Socio Bosque Program. The field phase was conducted between Februarysto March 2014.We analyzed data from one hundred twenty-two surveys of these two different groups of farmers. The analysis of information included data about geographical, social, labor, economic, land use and future activities. Among other results, it is evident that most owners want to keep their wooded areas with native species, but they mention the need for more frequent training about the dynamics of localecosystems and best ways to care for them.